2013
DOI: 10.14233/ajchem.2013.1410
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a New Allelochemical from Seeds of Adenanthera pavonina Linn.

Abstract: A new allelochemical (1), m.p. 282-284 ºC, m.f. C31H36O19, [M] + 712 (FABMS), has been isolated from methanolic extract of the seeds of Adenanthera pavonina Linn. alongwith two known compounds 2',4',7-trihydroxy isoflavone and isovitexin. The structure of a new compound was characterized as 3,5,7,3',4'-pentahydroxy flavone-3'-O-α-L-rhamnopyranosyl-(1→4)-O-α-L-arabinopyranosyl-(1→3)-O-β-D-xylopyranoside, by various colour reactions, spectral analysis and chemical degradations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Since the content of this phenolic compound determined in A. pavonina is rather higher in comparison with the amounts present in other plant foods such as fruits and vegetables (Wood et al, 2011), it is possible to suppose that regular consumption of the seeds can contribute to their previously described anti-inflammatory action and supports their uses in traditional medicine for the treatment of inflammation (Lim, 2012). Content figures for other the phenolic compounds analysed are significantly lower, not exceeding 80 µg/100 g. Our results describing the presence of flavonoid compounds in A. pavonina are in correspondence with the findings of Yadava and Vishwakarma (2013), who identified several flavonoids and flavonoid glycosides in seeds of this species form India. However, the presence of all the above-described phenolic compounds in this plant is reported for the first time in this paper.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Since the content of this phenolic compound determined in A. pavonina is rather higher in comparison with the amounts present in other plant foods such as fruits and vegetables (Wood et al, 2011), it is possible to suppose that regular consumption of the seeds can contribute to their previously described anti-inflammatory action and supports their uses in traditional medicine for the treatment of inflammation (Lim, 2012). Content figures for other the phenolic compounds analysed are significantly lower, not exceeding 80 µg/100 g. Our results describing the presence of flavonoid compounds in A. pavonina are in correspondence with the findings of Yadava and Vishwakarma (2013), who identified several flavonoids and flavonoid glycosides in seeds of this species form India. However, the presence of all the above-described phenolic compounds in this plant is reported for the first time in this paper.…”
Section: Resultssupporting
confidence: 89%
“…Several classes of biologically active secondary metabolites (e.g. flavonoids) have also been identified (Yadava and Vishwakarma, 2013). It has recently been shown that the processing of A. pavonina significantly affects the nutritional and anti-nutritional composition of seeds, and their milk extract contains higher amounts of certain minerals and vitamins compared to that from soybeans (Nwafor et al, 2017;Afolabi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of flavonoids in leaves, seeds, and barks of A. pavonina has been implicated in some biological effects of this herb (Zeid et al, 2012;Adedapo et al, 2014;Mujahid et al, 2015). Three flavonoid compounds were elucidated from the methanolic extract of the seeds of this plant: 3,5,7,3',4'-pentahydroxy flavone-3'-O-a-Lrhamnopyranosyl-(1→4)-O-a-L-arabinopyranosyl-1→3)-O-b-D-xylopyranoside (A) along with two known compounds 2,4,7-trihydroxyisoflavone (B) and isovitexin (C) (Appendix A1) (Yadava and Vishwakarma, 2013).…”
Section: Phytochemical Analysis Of Leavesmentioning
confidence: 99%